Memenuhi Hak Anak Berkebutuhan Khusus Melalui Pendidikan Inklusi - Ayu Zalni; Elna Yustiana; Resti Ayu Putri; Opi Andriani (Institut Nalanda, 2024)
This research describes the fulfillment of anqk with special needs in inclusive schools, this research aims to describe the rights of children with special needs (ABK, the type of research used is qualitative. The data collection technique uses interview and observation methods. The research subjects are class teachers, along with the head schools, research results indicate that children with special needs or (ABK) have partially received their rights, although they have not been fully fulfilled